Study on the application of thermal-meltable recovery of CFRP strand anchors - Zuo, Yize; Xu, Shanchang; Fan, Xin; Liu, Weiwei; Guan, Shuai; Jia, Ruixin; Tafsirojjaman, T. (Frontiers in Built Environment, 2025)
Conventional pressure-type anchoring systems face challenges such as difficulty in recovery, low recovery efficiency, and insufficient durability over long-term use. Although the single-use cost of Carbon Fibre Reinforced Polymer (CFRP) strand anchors is higher than that of conventional steel strands, recovery and reuse can significantly reduce costs. Therefore, this study aims to investigate the bonded anchoring method of CFRP and proposes an innovative thermoplastic CFRP prestressed strand design that combines both anchoring strength and recoverability to address the shortcomings of existing anchoring systems. Two bonding materials, thermosetting resin and thermoplastic resin, were selected for bond strength tests under different conditions. The results indicated that epoxy resin had a bonding force of 280 kN and an anchoring efficiency of approximately 70%, making it the most suitable material. However, the anchoring efficiency still needs improvement. Based on this, an improved design scheme was proposed, which can increase anchoring efficiency to over 95%. Additionally, based on the dispersed bonding anchor system, this study explored a solution that involves adding a positioning plate at the end of the anchor strand and using epoxy resin for anchoring. The anchoring performance tests showed that the tensile strength of the CFRP strand ranged from 2.7–2.8 GPa, with an average anchoring efficiency of 100.5%, demonstrating excellent anchoring performance. Further thermoplastic recovery tests showed that when the temperature increased to 90°C, the maximum recovery force of the strand was 17.2 kN, about 4.4% of the ultimate load. When the temperature increased to 150°C, the maximum recovery force was 7.5 kN. The recovered CFRP strands were clean, with no resin residue, and had no damage, maintaining an intact structure. The proposed thermoplastic CFRP prestressed strand design demonstrates significant advantages in anchoring strength and recoverability. With the improved design, anchoring efficiency can be increased to over 95%, and the high-temperature recovery process shows good feasibility. Compared with traditional anchoring systems, CFRP strands offer higher anchoring efficiency, lower recovery force requirements, better economics, and sustainability, making them a promising solution for engineering applications.